Fungsi Badan Narkotika Nasional (BNN) dan Polisi dalam Tindak Pidana Narkotika - I Made Karnadi; I Nyoman Gede Sugiartha; Ida Ayu Putu Widiati (Jurnal Preferensi Hukum, 2021)
Prevention of narcotics abuse by adolescents children and adults as well as the eradication of narcotics trafficking is handled by an institution namely the National Narcotics Agency and the Police The National Narcotics Agency has the authority to conduct investigations and investigations The police also have the same powers as the National Narcotics Agency The problems studied in this research are 1) The function of the National Narcotics Agency and the Police in narcotics crime 2) Synergy between the National Narcotics Agency and the Police in Investigation and Investigation of narcotics crime. The research method used in this research is normative legal research Besides that an approach through legislation is also used as well as a conceptual approach The results of this study indicate that the function of the National Narcotics Agency is the prevention and eradication of narcotics abuse Meanwhile the police function is to arrest conduct investigations and investigations and eradicate the illicit trafficking of narcotics The synergy between the National Narcotics Agency and the Police is carried out by means of coordination in dealing with narcotics crime Starting from the investigation investigation assessment of the perpetrator to the process of escorting hearing and execution